Growth of Mg2GeO4 nano-crystals on Si substrate and modulation of Seebeck coefficient by post growth annealing technique. Issue 13 (September 2019) - Rehman, A.; Jacob, Jolly; Zahra, R.; Mahmood, K.; Ali, A.; Rehaman, U.; Ali, Yasir; Ashfaq, A.; Ahmed, W.; Ikram, S.; Amin, N.; Hussain, S.
Abstract: We have reported the successful growth of Mg2 GeO4 nano-crystals by simple thermal evaporation technique. The Mg and Ge metal powders were evaporated on the Si substrate and kept the oxygen flow rate of 100 sccm. The modulation of structural, morphological, thermoelectric and electrical properties was performed by controlling the thermal energy of carriers using different annealing temperatures. XRD data showed a peak at 61.8 0 which was related to (212) plane of Mg2 GeO4 . XRD data further suggested that sample annealed at 700 °C has stable crystal structure while sample annealed at 800 °C posses degraded structure because the presence of highest density of donors defects. This defect concentration causes an increase in the conductivity of annealed samples as evident by the Hall data. This argument was also supported by Raman spectroscopy which showed that sample annealed at 700 °C has strongest Mg2 GeO4 Raman peak. SEM images also verified the smooth surface of the sample annealed at 700 °C. The temperature dependent (25–100 °C) Seebeck effect measurements were performed to calculate the Seebeck coefficient of Mg2 GeO4 nano-crystals at different measurement temperatures. The highest value of room temperature Seebeck coefficient (397 μV/ 0 C) for the sample annealed at 800 °C is due the high density of carrier concentration.